ETIKA DALAM ISLAM: TELAAH KRITIS TERHADAP PEMIKIRAN IBN MISKAWAIH - Rusfian Efendi (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2019)
The flow of ethical thought does not stop at Western Philosophy. Ethical thinking also colors and influences the discourse of thought in Islamic Philosophy. Differences in the style of Western Philosophy and Islamic Philosophy have a significant impact that has caused a debate about the expertise and courage of a Muslim thinker in adopting Greek ethical thought by not leaving the corridors of Islamic teachings. A very striking difference is the portion of the use of ratios in the construction of thought.One such debate is the difference of opinion regarding the contribution of Ibn Miskawaih in ethical discourse. Some Muslim thinkers say that Ibn Miskawaih is an ethical figure with his main work Tahdzib al-Akhlaq, while other opinions say that he is a moral figure. Thus, this research will show Ibn Miskawaih’s thought building in deeper, so that the foundations of his thought can be seen. More broadly, this research is important to be done to clarify the realm of moral and ethical discourse that develops in Islamic Philosophy, even though Western Philosophy and Islamic Philosophy have the same universal values.This study examines the book Tahdzib al-Akhlaq which is a Ibn Miskawaih master piece. This research attempts to answer the question whether Tahdzib al- Akhlaq is an ethical or moral book. This was done by examining two works of translation of Tahdzib al-Akhlaq, namely The Refinement of Character written by Constantine K. Zurayk and Towards Moral Perfection written by Helmi Hidayat. This research is focused on tracing the arguments compiled by Ibn Miskawaih and tracking the minds of the figures that influence them.From this research it was concluded that Tahdzib al-Akhlaq was not an ethical work, but a moral work. This affirms the criticism made by Fazlur Rahman that Muslim philosophers have failed to produce logically related ethical systems.